African Manufacturing SMEs Economic and Networking Abilities - (:unkn) unknown (My University, 2023)
Networking is very important strategic tool for SMEs survival and growth everywhere in the world. African manufacturing SMEs require proper networking strategy to enhance their economic contribution and employment creation. This chapter intends to outline various challenges facing African manufacturing SMEs economic performance and networking abilities. Various factors such lack of incubation and innovation, technology infrastructure, lack of political will and support, institutional policy support identified to be most critical for the survival of these industries. African governments should put financial resource as a priority and assist them with global markets access.
Keywords: African Research